Carbon tax incentive policy towards air passenger transport carbon emissions reduction. (August 2020) - Qiu, Rui; Xu, Jiuping; Xie, Heping; Zeng, Ziqiang; Lv, Chengwei
Highlights: A carbon tax incentive policy for air passenger transport is proposed. A bi-level model considering the conflicts of governments and airlines is developed. The genetic algorithm is combined with fuzzy logic controllers to solve the model. The incentive policy works in emissions reduction under proper conditions. Policy implications concerning the incentive policy are provided. Abstract: With the rapid expansion of the aviation industry, air passenger transport fossil fuel consumption and carbon emissions have attracted increasing attention. To reduce fossil fuel consumption and carbon emissions, this paper investigates an air passenger transport carbon tax incentive policy setting problem, in which the carbon tax incentive policy includes a carbon tax and competitive tax rebates. Then a bi-level programming model is proposed to solve this problem. An interactive solution approach combining a genetic algorithm with fuzzy logic controllers is developed to find solutions based on the ICAO and airlines related data. The results indicate that the incentive policy could encourage airlines to improve fuel consumption and emission performance under proper conditions. Besides, the government should effectively control the carbon tax incentive level based on application effect and financial support, and airlines could select proper improvement strategies and carbon tax transfer ratios under the incentive policy.